2007
DOI: 10.1128/cvi.00043-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Simplified Dual-Platform Flow Cytometric Method for Measurement of Lymphocyte Subsets and T-Cell Maturation Phenotypes in the Population of Nouna, Burkina Faso

Abstract: In the context of a larger clinical study in Nouna, Burkina Faso, we evaluated a simplified dual-platform (DP) flow cytometric (FCM) method that allows the determination of major lymphocyte subsets in a single test tube. We compared the phenotyping of lymphocytes with DP FCM and simultaneous measurements with standard single-platform (SP) FCM for samples from 177 individuals. Analysis of the comparative measurements revealed that DP FCM systematically underestimates the proportion of NK cells, overestimates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Boolean gating analysis identified 16 subpopulations expressing each possible combination of markers within the CD4 T cell population (Figure 1, gating strategy is shown in Figure S1). In all groups, approximately 26% of CD4 T cells could be defined as naïve as they expressed all 4 markers, in agreement with previous studies on healthy individuals in the United States [22] and Burkina Faso [23].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Boolean gating analysis identified 16 subpopulations expressing each possible combination of markers within the CD4 T cell population (Figure 1, gating strategy is shown in Figure S1). In all groups, approximately 26% of CD4 T cells could be defined as naïve as they expressed all 4 markers, in agreement with previous studies on healthy individuals in the United States [22] and Burkina Faso [23].…”
Section: Resultssupporting
confidence: 91%
“…Collectively, our data suggest that environmentally triggered T cell activation in rural Kenya does not seem to drive the general exhaustion of CD4 T cells, despite significantly higher levels of reported chronic and acute conditions in the rural as compared with the urban setting [26]. Earlier studies, using only CD45RA and CCR7 or CD27 as markers, found more memory and fewer naïve T cells in PBMC of African compared to European donors [23], [25], [27]. We did not observe similar skewed distribution of CD4 T cell phenotypes, when 4 markers were used to distinguish CD4 T cell types.…”
Section: Resultsmentioning
confidence: 48%
“…Sites 1 and 4 showed higher CD4+ and CD8+ cell counts for single-platform than for dual-platform, a finding reported in other studies (11,12). …”
Section: Resultssupporting
confidence: 83%
“…CD4 + and CD8 + naïve and memory T cell subsets were assessed with anti-CD4 or anti-CD8-PerCP, anti-CD45RA-FITC and anti-CCR7-PE conjugated monoclonal antibodies as described [10]. Naïve T cells were identified as CD45RA bright CCR7 + CD4 + or CD8 bright lymphocytes [18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we had observed significant differences in the distribution of T cell maturation phenotypes between healthy adults in Burkina Faso [10] and published data from populations in Europe [11]. In the few studies that have addressed the immunological consequences of HIV-1-infection in Africans, the focus has been directed towards the expression of CD38 on CD8 + T cells [12][13][14].…”
Section: Introductionmentioning
confidence: 99%